2015
DOI: 10.20510/ukjpb/3/i5/89506
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Different Levels of Eucalyptus Oil: An In Vitro Trial to Study the Effect on Sheep Rumen Methanogenesis and Fermentation Processes

Abstract: An in vitro trial was conducted in fermentation vessels under anaerobic conditions using composite feed-1 and composite feed-2 with inclusion of different levels of Eucalyptus oil (EO) along with buffered rumen liquor of sheep to observe the effects of oil on rumen methanogenesis and fermentation. The CF-1 consisted of 40% of concentrate and CF-2 had 25 % of concentrate.The various concentrations of EO used in present study were 0.5,1 and 2 µl/ml. During the present investigation it was observed that on increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Mukharji and Srivastava [38] described a reduction in gas production, methane, and total VFA concentration, and an increase in propionate molar proportion in response to the addition of eucalyptus oil. These changes in VFA concentrations deserve further investigation as, in our study, the concentrations of acetate and propionate and the acetateto-propionate ratio were different among eucalyptus species and seasons.…”
Section: Discussionmentioning
confidence: 99%
“…Mukharji and Srivastava [38] described a reduction in gas production, methane, and total VFA concentration, and an increase in propionate molar proportion in response to the addition of eucalyptus oil. These changes in VFA concentrations deserve further investigation as, in our study, the concentrations of acetate and propionate and the acetateto-propionate ratio were different among eucalyptus species and seasons.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that addition of ANI decreased in vitro total VFA concentration, NH 3 -N concentration, and the proportions of acetate and propionate (Busquet et al, 2005;Busquet et al, 2006;Cardozo et al, 2006). The inclusion of the EUC in an in vitro trial decreased the total VFA and NH 3 -N concentration, methane emission, and GP, even at 0.5 mL/L concentration (Mukharji and Srivastava, 2015). Those results are mostly consistent with the addition of ANI and EUC in the current study except for the increased proportion of propionate.…”
Section: In Vitro Experimentsmentioning
confidence: 96%